Step-by-step explanation:
step one:
The question is actually incomplete, but we can make do with information we have.
step two:
seeing that this is a word problem, we need to convert the statement to mathematical expression.
1. t decreased by 4 is (t-4)
2. 8 more than t (t+8)
step three:
therefore the product of t decreased by 4 and 8 more than t
= (t-4)*(t+8)
we can proceed by opening the brackets
[tex]=t(t+8)-4(t+8)\\\\=t^2+8t-4t+32\\\\[/tex]
collecting like terms we have
[tex]=t^2+8t-4t+32\\\\=t^2+4t+32[/tex]